BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN DIET PENDERITA DIABETES MELLITUS - Nilam Noorma; Lia Kurniawati; Ismanilda Ismanilda; Lukman Waris (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Diabetes mellitus (DM) is a chronic disease characterized by elevated blood glucose levels due to impaired insulin production, impaired insulin action, or a combination of both. The objective of this study was to identify factors associated with dietary adherence among patients with diabetes mellitus. A cross-sectional study design was used. The study was conducted in the service area of the Medan Sunggal Community Health Center. The study was carried out in April 2025. The study population consisted of all patients with type 2 DM registered at the Medan Sunggal Community Health Center. The study sample comprised 55 respondents. Purposive sampling was used. The research instrument was a questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed a significant association between attitude (p-value: 0.027) and family support (p-value: 0.000) and dietary compliance among patients with type 2 diabetes. It is recommended that patients with type 2 diabetes continue to improve their health by regularly monitoring their blood sugar levels, following a blood sugar-controlled diet, and exercising regularly so that their quality of life will improve.Keywords: Type 2 DM, Family Support, Attitude.